2019
DOI: 10.1002/bse.2369
|View full text |Cite
|
Sign up to set email alerts
|

Boundary‐spanning search and firms' green innovation: The moderating role of resource orchestration capability

Abstract: Building on resource-based theory and resource orchestration theory, we investigate the impact of two characteristics of boundary-spanning search, search breadth and search depth, on firms' exploitative and exploratory green innovations. We also examine the moderating role of resource orchestration capability. The results of data analysis from 186 manufacturing firms in China show that both search breadth and search depth have inverted U-shaped relationships with exploitative and exploratory green innovations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
157
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 132 publications
(171 citation statements)
references
References 93 publications
(162 reference statements)
14
157
0
Order By: Relevance
“…With the required green expertise, team members might exert relevant knowledge to solve a domainspecific green task challenge (Sasidharan, 2018). However, by employing green creativity skills, team members may efficiently utilise prior green expertise in distinct ways to address a specific complex challenge, effectively manage projects and save time and resources (Gube & Lajoie, 2020;Wang et al, 2019). In this regard, green creativity skills could help team members amplify their respective green expertise implementation via extensive exploration of several novel cognitive pathways stemming from prior experience or knowledge (Gube & Lajoie, 2020).…”
Section: The Mediating Role Of Green Creativity Skills Between Green Expertise and Goiementioning
confidence: 99%
“…With the required green expertise, team members might exert relevant knowledge to solve a domainspecific green task challenge (Sasidharan, 2018). However, by employing green creativity skills, team members may efficiently utilise prior green expertise in distinct ways to address a specific complex challenge, effectively manage projects and save time and resources (Gube & Lajoie, 2020;Wang et al, 2019). In this regard, green creativity skills could help team members amplify their respective green expertise implementation via extensive exploration of several novel cognitive pathways stemming from prior experience or knowledge (Gube & Lajoie, 2020).…”
Section: The Mediating Role Of Green Creativity Skills Between Green Expertise and Goiementioning
confidence: 99%
“…The construct validity was assessed by conducting the exploratory factor analysis with maximum variance rotation. The results indicated that five factors with eigenvalues above 1 were extracted, and the factor loadings were greater than 0.60, demonstrating acceptable construct validity (Wang et al, 2020a). Moreover, we applied a confirmatory factor analysis to EJIM 24,4 assess construct validity.…”
Section: The Analysis and Resultsmentioning
confidence: 92%
“…That is, for firms with high GAC, they are better at developing and improving GKIC by LEL, further promoting GI. (Arfi et al, 2018;Cainelli et al, 2015;Du et al, 2018;Wang et al, 2020a), collaboration with supply chain partners (Zhao et al, 2018;Melander, 2018;Ardito et al, 2019) and relationship learning (Albort-Morant et al, 2016Leal-Mill an et al, 2016) can promote GI. Interestingly, we find that the influence of VEL on GI is greater than LEL.…”
Section: Hypotheses Testingmentioning
confidence: 99%
See 2 more Smart Citations